L’exploitation minière dans la vallée du Chassezac (Ardèche) - Marie-Christine Bailly-Maître; Nicolas Minvielle Larousse; Éric Kammenthaler; Thierry Gonon; Guergana Guionova (Archéologie Médiévale)
In Europe, the period from the middle of the 10th century to the middle of the 14th century sees a marked expansion in all sectors of activity. To meet new needs, ores are actively sought after. Silver, necessary for coinage, is of primary importance. The mining district which developed on the edge of the Chassezac river provides an opportunity to study a group of extraction sites, preserved in their medieval state (11th-13th centuries), associated with a true “industrial quarter” comprising ore-treatment workshops.This assemblage is not an isolated example and leads to consideration of the place and role of precious-metal mining in the formation of territories and their political control in the south of France.